Relationship between online cognition and personality traits: A questionnaire based study of medical college students. (13th April 2021) - Ohri, N.; Gill, A.; Vankar, G.; Tyagi, P.; Reddy, S.
Abstract : Introduction: Current classification systems are not sure where to place the internet use disorder. Is it an addiction, an impulse control disorder, a consequence of another psychiatric morbidity or a consequence of personality trait/personality disorder? Objectives: We intended to study which personality traits associated with online cognition may contribute towards Problematic internet use(PIU). We also analysed the relationship between number of hours of use/week of internet and PIU along with its relation with two 'screening' questions. Methods: Online cognition scale and Abbreviated Eysenck Personality questionnaires were our measurements of choice in addition to demographic measures and some questions pertaining to online behaviour patterns. Results: Total 163 responses were analysed. The demographic pools consisted mostly of young adults who had, on average, used the internet for 5.2 years at present rate of 21.81hours/week. We observed significantly higher mean OCS scores in men, in people who thought that the internet interfered with their lives and in those who felt the need to 'cut-down'. A moderate positive and significant correlation was observed between hpurs/week of internet use and OCS scores. Also, significant positive correlation was observed between Neuroticism and OCS, impulsivity, and loneliness/depression scores. Significant negative correlations were observed between the Lie trait and impulse control. Neuroticism and Lie together contributed to 21.8% of variance in OCS scores. Conclusions: Neuroticism and Lie traits (representing need for social acceptance) were found to the causing significamn varience in the OCS scores of the subjects. High number of hours/week use of internet was related to the feeling of 'need to cut down use'.